TP011/#1527 GOG 3039 a phase II study of abemaciclib in combination with letrozole in advanced, recurrent or metastatic endometrioid endometrial cancer. (4th December 2022) - Huang, Marilyn; Huang, Gloria; Sill, Michael; Lewin, Sharon; Gill, Sarah; Lankes, Heather; Coleman, Robert L; Slomovitz, Brian
Abstract : Objectives: Primary Objective: To evaluate the efficacy in terms of the probability of surviving progression free for at least 6 months (PFS at 6 mo). Secondary Objective: To determine the proportion responding by RECIST v1.1 in patients with advanced, persistent, or recurrent endometrioid endometrial cancer. To estimate the time to disease progression or death (PFS and OS endpoints). To describe the toxicities in patients receiving combination therapy with letrozole and abemaciclib with advanced/metastatic endometrial cancer. Methods: Key Eligibility Criteria:-Advanced (FIGO 2014 Stage III or IV), persistent, or recurrent endometrial carcinoma -Must have endometrioid histology (all grades allowed) (Hormone receptor status is not required for enrollment). -Must have measurable disease by RECIST v1.1. -Prior chemotherapy in the adjuvant setting for Stage I, II, or III is permitted. -Prior chemoradiotherapy for a pelvic recurrence is permitted. -Prior immunotherapy and/or targeted therapy is allowed in addition to, in combination with, in lieu of, or subsequent to prior chemotherapy. Regardless of circumstances, no more than one prior chemotherapy regimen (including chemo-radiotherapy) is permitted, and no more than one additional systemic therapy is permitted. Hence, eligible patient may have received 0, 1, or 2 prior lines of systemic therapy and for women who received two prior lines of therapy, only one of them may have included chemotherapy. -ECOG performance status of 0–1. -Must be able to swallow oral medications. Results: Trial in progress: there are no available results at the time of submission. Conclusions: Trial in progress: there are no available conclusions at the time of submission.